Structural and Electronic Reconstructions at the LaAlO3/SrTiO3 Interface (Adv. Mater. 16/2013). (18th April 2013) - Salluzzo, M.; Gariglio, S.; Torrelles, X.; Ristic, Z.; Di Capua, R.; Drnec, J.; Sala, M. Moretti; Ghiringhelli, G.; Felici, R.; Brookes, N. B.
<x xml:space="preserve">Abstract</x> Illustration of a synchrotron‐radiation X‐ray experiment on a LaAlO3/SrTiO3 heterostructure: Absorption of linear polarized photons is used to determine the orbital splitting of 3d orbitals (upper‐right) of titanium ions (red spheres); surface X‐ray‐diffraction allows a structural refinement of the systems. M. Salluzzo and co‐workers combine these two techniques on page 2333 to reveal a structural and electronic reconstruction of the interface, correlated to the formation of a two‐dimensional electron gas. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>